Warfarin and the apparent minor head injury. Issue 3 (May 1996) - Saab, M; Gray, A; Hodgkinson, D; Irfan, M
Abstract : Two cases of patients on warfarin who developed intracranial haematoma after an apparently minor head injury are described. There is a 10-fold increase in the likelihood of developing an intracranial haematoma in these patients. Recommendations are made regarding the management of this type of patient seen in the accident and emergency department.